PENGETAHUAN DASAR IBU-IBU RUMAH TANGGA TERHADAP PENYALAHGUNAAN FORMALIN UNTUK PENGAWETAN MAKANAN - Muhammad Ilyas (Asian Journal of Innovation and Entrepreneurship, 2018)
The problem of food insecurity that has occurred in Indonesia has the potential to become a national food problem if it is not handled seriously. The issue of chemical pollution not only stops on marine products, but also has spread on agricultural products and processed food products. This means that the chain of harmful food products involving fishermen, farmers, processed food businessmen and consumers as end users of these products. Formalin is one of chemicals that allegedly contaminate marine products and processed food products. The use of prohibited chemical substances by producers is not solely driven by economic motives to cut production costs but also influenced by food safety knowledge among users. Distribution of harmful food not only harm the right of consumers to get a healthy and safe food. But it also puts consumers especially those who have a low level of food safety knowledge as a group at high risk for the attack of various diseases in the future. In general, the respondents' responses, housewives to the question items used for the housewife's basic knowledge of formalin abuse for food preservation, illustrate basic knowledge of housewives in Sleman District. In detail on the question items about formaldehyde to preserve food, the formalin effect on health, formalin for preserving marine products, the characteristics of fresh fish containing no formaldehyde, and know characteristics that do not contain formalin, the knowledge of the respondents is good enough. This is evidenced by the percentage of approval numbers on the questions posed. The basic knowledge of formalin to preserve food shows a 66% approval rate, about 92% health formalin impact on formalin to preserve marine products by 80%, about the characteristics of fresh fish without formaldehyde by 72%, characteristic of tofu that does not contain formalin by 90%.